2013
DOI: 10.1016/j.fertnstert.2013.02.056
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization with single euploid blastocyst transfer: a randomized controlled trial

Abstract: In women ≤ 42 years old, transferring a single euploid blastocyst results in ongoing pregnancy rates that are the same as transferring two untested blastocysts while dramatically reducing the risk of twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
362
3
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(376 citation statements)
references
References 36 publications
4
362
3
7
Order By: Relevance
“…There are various PGS methods for comprehensive chromosome screening currently in clinical use, including comparative genomic hybridization (array-CGH) (4,5), single-nucleotide polymorphism (SNP) arrays (6-9), multiplex quantitative PCR (10), and next-generation sequencing (NGS) (11,12). Multiple clinical trials have confirmed the clinical efficacy of PGS, including increasing implantation and clinical pregnancy rates, as well as decreasing miscarriage rates (13)(14)(15)(16). However, the applicability of PGS has been limited for a number of reasons:…”
mentioning
confidence: 99%
“…There are various PGS methods for comprehensive chromosome screening currently in clinical use, including comparative genomic hybridization (array-CGH) (4,5), single-nucleotide polymorphism (SNP) arrays (6-9), multiplex quantitative PCR (10), and next-generation sequencing (NGS) (11,12). Multiple clinical trials have confirmed the clinical efficacy of PGS, including increasing implantation and clinical pregnancy rates, as well as decreasing miscarriage rates (13)(14)(15)(16). However, the applicability of PGS has been limited for a number of reasons:…”
mentioning
confidence: 99%
“…In our database, 31.8 % (139/437) of patients who sent samples to Reprogenetics for CCS met this criteria. Furthermore, in the randomized controlled trial of SET following CCS versus DET of unbiopsied embryos by Forman et al [32] the average number of surplus euploid embryos following a SET was 3.2. Thus, a significant number of patients meet this criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it stands to reason that achieving a larger cohort of confirmed euploid blastocysts would be similarly associated with higher pregnancy rates. In Forman et al [32] for example, the average number of confirmed euploid blastocysts remaining following SET was 3.2. This suggests a surplus of euploid embryos may have been a marker for the excellent outcomes seen following SET in this study.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The three earliest RCTs which are often cited as sound evidence in favour of PGS [68][69][70] have however been heavily criticized [12]. The main criticisms are the small size of the study [68], the fact that transfer of cryopreserved embryos which could have been higher in the control group was not taken into account and could have led to additional pregnancies [68,70], the inclusion of good prognosis patients only with at least a number of analysable embryos, the difference in number of embryos transferred between the two study groups and finally the use of implantation rate as outcome measure [69,70]. These trial characteristics lead to a distortion of the real a priori benefit for patients, as they do not represent those patients that for instance do not obtain blastocysts for analysis, or only have abnormal embryos and therefore do not even reach embryo transfer.…”
Section: Pgs and Its Troubled Relationship With Evidence-based Medicinementioning
confidence: 99%